Light and strong SiC networks - Ferraro,C; Garcia-Tuñon,E; Rocha,VG; Barg,S; Fariñas,MD; Alvarez-Arenas,TEG; Sernicola,G; Giuliani,F; Saiz,Gutierrez E (Advanced Functional Materials, 2016)
The directional freezing of microfiber suspensions is used to assemble highly porous (porosities ranging between 92% and 98%) SiC networks. These networks exhibit a unique hierarchical architecture in which thin layers with honeycomblike structure and internal strut length in the order of 1–10 μm in size are aligned with an interlayer spacing ranging between 15 and 50 μm. The resulting structures exhibit strengths (up to 3 MPa) and stiffness (up to 0.3 GPa) that are higher than aerogels of similar density and comparable to other ceramic microlattices fabricated by vapor deposition. Furthermore, this wet processing technique allows the fabrication of largesize samples that are stable at high temperature, with acoustic impedance that can be manipulated over one order of magnitude (0.03–0.3 MRayl), electrically conductive and with very low thermal conductivity. The approach can be extended to other ceramic materials and opens new opportunities for the fabrication of ultralight structures with unique mechanical and functional properties in practical dimensions.